Cultural effects on the space efficiency of hospitals in Davao City - Nacorda, Marneille T. (2004)
The hospital that the current generation enjoys now is a product of complex needs figured, studied and answered by a lot of designers. Standards were even formulated to meet such. From the floor to the ceiling to even the tiniest handle that had any contact with the users are carefully planned. Technicalities of health care facilities were once the main focus of the latter's design. However as time pass by, effects of the user's behavior were given attention. Such were found out by many studies that it has a great impact on the totality and efficiency of the hospitals. Currently, concepts like healing architecture, medical mall concept and cruciform arrangement were adapted. From the probing conducted by certain designers on such, findings show that they indeed enhance the whole personality of the healthcare facilities. Nevertheless, application of the said concepts on a certain area must undergo further study for it might not function as it has been where it has actually been used and applied. From the query conducted, a new concept came to exist, which was the answer to the problems identified in the existing hospitals in the city. This formulated concept, which has been the basis for the design of a new general tertiary hospital was the medical mall concept.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2004